Cultural Representation in EFL Textbooks for the Seventh Graders: A Multimodal Analysis - Fransiska Prihatiningsih; Ismail Petrus; Sary Silvhiany (Lingua Cultura, 2021)
The research aimed to investigate a types of cultures represented in the EFL textbooks for the seventh graders. Two EFL textbooks were analyzed: ‘When English Rings a Bell’ and ‘English on Sky 1’. The research applied a qualitative content analysis as method and Kress and van Leeuwen’s multimodal social semiotic approach as the technique of analyzing data. The result reveals that imbalances in the representation of cultural types exist. Source culture is represented more dominantly compared to target and international culture. It implies that both the authors and the publishers of the textbooks prioritize the learners’ identities construction and characters education rather than focus on the use of language as the lingua franca. Consequently, it could constrain the opportunities for learners to acquire international cultural knowledge and become successful intercultural communicators. Therefore, English teachers need to take an active role in selecting appropriate textbooks and adding supplementary materials or activities to patch up the shortcomings of the textbooks.